Characterizing methane emissions from orphaned coalbed methane wells in the powder river basin - J Nivitanont; E P Robertson; S M Murphy; M D Burkhart; D R Caulton (Environmental Research Communications, 2023)
In 2018, the U.S. EPA Greenhouse Gas Inventory (GHGI) began including methane emissions from abandoned oil and gas (AOG) wells and estimated that they may constitute up to 4% of total methane emissions from the oil and gas sector. Several studies have shown that these emissions vary by location which introduces regionally dependent uncertainty into inventory estimates. In Wyoming, there are over 1000 wells identified as ‘orphaned’ indicating that they are both abandoned and unplugged, approximately 80% of which are coalbed methane (CBM) wells. In this pilot study, 3-hour measurements of ten orphaned CBM wells were taken to support the characterization of AOG well emission rates in the Powder River Basin (PRB) in Wyoming. The mean methane emission rate measured at these wells was 653 mg CH _4 /hr with the majority of these wells emitting in the 100-1000mg CH _4 /hr range. The highest emitting well in the study was measured at 4.53 g CH _4 /hr. Compared to the GHGI AOG wells emission factor of 10.04 g CH _4 /hr, these findings suggest that AOG wells emission rate in the PRB are overestimated by national inventory methods. Finally, the addition of AOG well emissions data from this study doubles the number of sampled AOG wells in Wyoming and triples the number of sampled CBM wells in the U.S.